Pengaruh Variasi Konsentrasi Perekat Terhadap Massa Bahan Baku Pada Daur Ulang Karton Kemasan Aseptik - Arga Aflyn Febrina H; Elvi Yenie; Aryo Sasmita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Waste problem is a complicated problem in Indonesia; aseptic packaging waste is one of them. This study student tried to recycle paper carton aseptic packaging into paper art. The purpose of this study was to learn how variations of adhesive influence raw material mass in the process of aseptic packaging waste into art paper, to analize the quality of the result on its grammature test, tearing strength index, tensile strength index, and the bursting strength index Student used 50gr of raw material mass and variations of 5%, 7.5% and 10% of PVAC adhesive. The results of generated paper art then tested in the laboratory of paper to determine its Grammature, Tearing strength index, Tensile strength index, and the Bursting strength index. The best results for Grammature determination at 10% adhesive concentration is 352 g. The best result for Tensile strength index at 10% adhesive concentration is. 7.56mN. The best results for Tearing strength index 10% adhesive concentration is 4776 kN / m and the best results for Bursting strength index is 545.84 kPa. Overall the paper art produced, including in both categories in accordance with the quality standards of food packaging cardboard and paper.Keywords: Aseptic packaging waste, PVAC adhesive, Recycling, Paper art